« Traduit du riddleyspeak (Anterre) par Nicolas Richard » : quand le traducteur se fait lecteur de science-fiction - Elaine Després (ReS Futurae)
Riddley Walker (1980) by the American-born British author Russell Hoban has become a cult post-apocalyptic science fiction novel over the years, and the language in which it is written, riddleyspeak, is no stranger to it. A veritable science-fictional novum, this defamiliarizing language-fiction (Sorlin, 2010), mixing English and Cockney, written and spoken, past and future, religion and science, has given the novel a reputation for being untranslatable. However, with Enig Marcheur (2012), Nicolas Richard has produced a genuine science-fictional and poetic translation in « parlénigm ». This article proposes to show that the translator’s proposal enriches and complexifies the xenoencyclopedia of Hoban’s novel rather than replacing it, almost bringing it to the side of transfictionality (Saint-Gelais, 2011) : the characters and the narrative are recognizable, but they exist in a different, even less familiar fictional and linguistic world. Using the analytical tools developed by Alice Ray (2019), we will explore this novum that is « parlénigm » through a comparative analysis of texts, the techniques employed by the translator, the effects produced, and other examples of language-fiction translation.